On the Meaning of Exhibitions - Exhibition Epistèmes in a Historical Perspective - Kerstin Smeds (Stockholm University Press, 2012)
This essay aims at contributing to our understanding of the nature of exhibitions, namely how and why we make them, and what they - and the things in them - might symbolize. My focus will be on exhibitions of objects in classical museums of cultural history, archaeology and ethnology/ethnography. I will discuss how scientific epistemologies and discourses, as well as the history of ideas and ideologies, are reflected in the way museums and exhibitions are organized. Theoretically, I will lean on ideas of Michel Foucault presented in his work The Order of Things (Foucault, 1991) and Power/Knowledge (Gordon 1980), but also on Mieke Bal's Double Exposures (1996), and a few others.